Pengaruh Realisasi Anggaran Hibah dan Anggaran Bantuan Keuangan terhadap Pertumbuhan Ekonomi - Utari, Sherina Putri; Ishak, Jouzar Farouq; Rufaedah, Yanti; Gunawan, Arwan (Indonesian Accounting Literacy Journal, 2024)
This study aims to determine the relationship between grant budget realization and financial assistance budget realization on regional economic growth in West Java Province. The realization of the grant budget and the realization of the financial assistance budget which continues to decline are often associated with economic growth which continues to increase. The method in this study is a quantitative method with data collection through secondary data derived from regional government financial reports and primary data in the form of interviews with the Regional Secretariat of West Java Province. The data analysis technique used is descriptive quantitative analysis using the Statistical Package for the Social Sciences (SPSS) version 25 tools. The results of the analysis show that the realization of the grant budget has no significant effect on economic growth in West Java Province as well as the realization of the financial assistance budget which has no significant effect on economic growth.